Plagiochila meagheriana (Plagiochilaceae: Marchantiophyta), a new species with dimorphic leaf cells from Darjeeling District, Eastern Himalaya, India - Majumdar, Shuvadeep; Dey, Monalisa (Phytotaxa, 2025)
A new species of Plagiochila (Dumort.) Dumort., Plagiochila meagheriana sp. nov.  characterized by having much longer than wide, horizontally spreading rectangulate leaves with truncate apices, both dorsal and ventral stem surface exposed, dimorphic cells in leaves of younger and older portion of the shoot, and lacking basal vitta-like area in leaf cells is described from Darjeeling district of West Bengal in Eastern Himalaya, India. It has been placed under Section Peculiares Schiffn. due to the presence of Peculiares-type vermiculate leaf cells.